2012
DOI: 10.1007/s10461-012-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Reliability and Validity of the Internalized AIDS-Related Stigma Scale in Rural Uganda

Abstract: HIV infection remains highly stigmatized throughout sub-Saharan Africa despite the increasing availability of treatment. HIV-related stigma is commonly described to be highly prevalent in East Africa, but none of these studies have employed validated scales for measurement. We used data from 456 people living with HIV/AIDS in rural Uganda to validate the six-item Internalized AIDS-Related Stigma Scale. The scale demonstrated acceptable internal consistency (Cronbach’s alpha=0.73) and time stability. Explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 61 publications
2
62
2
Order By: Relevance
“…Five articles were psychometric assessments of measurements and analysed correlates of internalised stigma as part of construct validity checks (Holzemer et al, 2007;Kalichman et al, 2009;Kingori et al, 2013;Tsai et al, 2012;Visser et al, 2008). Three articles aimed to assess predictors of another outcome and assessed correlates of internalised stigma as part of exploratory analyses to inform more complex modelling of other outcomes (Neuman & Obermeyer, 2013;Pearson et al, 2009;Simbayi et al, 2007b).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five articles were psychometric assessments of measurements and analysed correlates of internalised stigma as part of construct validity checks (Holzemer et al, 2007;Kalichman et al, 2009;Kingori et al, 2013;Tsai et al, 2012;Visser et al, 2008). Three articles aimed to assess predictors of another outcome and assessed correlates of internalised stigma as part of exploratory analyses to inform more complex modelling of other outcomes (Neuman & Obermeyer, 2013;Pearson et al, 2009;Simbayi et al, 2007b).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The most common measurement used in seven included articles was the Internalized AIDSrelated Stigma Scale (IA-RSS), developed by Kalichman and colleagues (2009) (Cloete et al, 2008;Kalichman et al, 2009;Peltzer, 2012;Simbayi et al, 2007b;Takada et al, 2014;Tsai et al, 2012;Tsai, Bangsberg, Bwana, et al, 2013). Five articles (Cuca et al, 2012;Holzemer et al, 2007;Makoae et al, 2009;Nattabi et al, 2011;Sorsdahl et al, 2011) reported use of the negative self-perception subscale of the HIV/AIDS Stigma Instrument-PLWA (HASI-P).…”
Section: Internalised Hiv Stigma Measurement Validity and Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Stigma was measured with the six-item Internalized AIDS-Related Stigma Scale which was found to yield high levels of reliability and validity in Africa (Kalichman et al, 2005(Kalichman et al, , 2009Tsai et al, 2013). A dichotomous response scale was used, that is, "agree" versus "disagree".…”
Section: Hiv-stigmamentioning
confidence: 99%